Analisa kinerja keuangan: Analisa perbedaan kinerja keuangan bank syariah dan bank swasta umum - Maria Esomar (Politeknik Kutaraja, 2021)
The era of digitalization presents a challenge for the banking industry, bank credit growth has decreased in 2019, therefore it is important to analyze bank financial performance. The purpose of this study is to examine the differences in the financial performance of Islamic banks in Maumalat and commercial private banks of MNC Bank by using financial ratios, namely the ratio of NPL, ROA, BOPO and FDR ratio. The data used are secondary data in the form of quarterly financial reports for 2019 and 2020 which are published on the website www.idx.co.id. Hypothesis testing is done by using the independent sample t test. The results of the analysis show that there are differences in financial performance between the MNC commercial private banks and the Muamalat Islamic bank as seen from the NPL and ROA ratios, while the financial performance as measured by the BOPO and FDR ratios shows no difference.